AN ANALYSIS OF DISCOURSE STRUCTURE OF BROMO PODCAST IN YOUTUBE CHANNEL - Juli, Juli; Tjahyadi, Indra (Program Studi Bahasa Inggris, Universitas Panca Marga, 2023)
This research is about the study of discourse in the Bromo Podcast Episode podcast